IMPLEMENTATION OF A WHISTLEBLOWING SYSTEM ON FRAUD DETECTION AT PT JR (CASE STUDY ONE OF STATE OWNED ENTERPRISES IN INDONESIA) - Rahman, Budi (Dinasti Publisher, 2020)
Reporting system or whistleblowing system is a means for whistleblower to report fraud or violations committed by internal organizations. This system aims to uncover fraud that can harm the organization and prevent even more fraud. This research is a case study at PT JR with the aim of this research is to find out the implementation of the whistleblowing system on fraud deetection at PT JR. The method used in this study is a combination method or mix methods. Data collection techniques using triangulation methods, namely quantitative data collection through questionnaires while qualitative through interviews and documents. Analyze data with a descriptive approach to get a real picture of the whistleblowing system at PT JR. The study population is an internal auditor at PT JR with the results of the study showing that the Whistleblowing System has a positive and significant effect on Fraud Detection.